Rozvoj v pohybu. Souvislosti a důsledky transnacionální migrace Romů a Romek z okresu Rimavská Sobota / Rimaszombat (Slovensko) do Grazu (Rakousku) - Benedik, Stefan; Szénássy, Edit; Tiefenbacher, Barbara (Romano džaniben, 2011)
Especially since the latest two EU-enlargements, the perception of Roma/Romnija in “western” European states is predominantly linked with forms of migration that emerged in post-communist countries. Still, these migrations are not unidirectional and homogeneous, but contain multi-layered and diverse forms of movement. In this paper we aim present some outcomes of a recent research-project, during which we analyzed movements from Romani communities in southern Slovakia to the Austrian province of Styria. The discussed Romani communities are not separated from their mostly Hungarian surroundings, either linguistically or in terms of housing. Nevertheless, the migrations and, moreover, their effects foster differentiation and partly even increase segregation. Some NGO projects in the region and the depiction in Austrian media in particular intensified othering of these Slovakian/Hungarian Roma/Romnija.